The impact of individualized and collective care for persons with disabilities on enhancing effective communication in society: A field study on a sample of parents in Algiers City - SAOUD, Fatima; GUEDDOUCHE, Salima (The International tax journal, 2026)
This study aims to investigate the impact of individualized and collective care patterns for persons with disabilities on enhancing effective social communication within society. The field study was conducted in Algiers, the capital city of Algeria, with a sample of 280 participants, including persons with disabilities, community members, parents, caregivers, and specialists. The research adopted a mixed-methods approach using a sequential explanatory design. Quantitative data were collected primarily through a questionnaire comprising 45 items distributed across four axes, based on a five-point Likert scale. Qualitative data were gathered via semi-structured interviews with a subsample of 20 participants. Quantitative data were analyzed using SPSS software, employing descriptive statistics, t-tests, analysis of variance (ANOVA), correlation coefficients, and multiple regression analysis. Qualitative data were analyzed thematically. The results revealed statistically significant differences in the availability and effectiveness of care patterns, favoring collective care over individualized care. Furthermore, a strong positive correlation was found between the level of care—particularly collective care—and the level of effective social communication. Multiple regression analysis confirmed that collective care serves as a primary explanatory variable in improving indicators of social interaction, acceptance of others, and community participation, whereas the impact of individualized care remained relatively limited.